Strategies to Address Red Tide Events in Florida: Results of a 2010 Survey of Coastal Residents - Sherry L. Larkin; Kristen M. Lucas; Charles M. Adams; John Stevely (EDIS)
Residents in coastal communities might oppose programs for preventing, controlling, or mitigating the effects of these harmful algal blooms if they would increase costs to residents or would cause harm to other aspects of the marine environment. This 5-page report presents the results of a survey intended to help summarize public opinion, inform policy makers, and evaluate possible programs for use in Florida. Written by Sherry L. Larkin, Kristen M. Lucas, Charles M. Adams, and John Stevely and published by the UF Department of Food and Resource Economics, April 2011.